ANALISIS INDUSTRI KECIL UNGGULAN DI KOTA PEKANBARU - Pebrianita Br Pinem; Harlen '; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the city of Pekanbaru with the object of research areas 12 districts in the city of Pekanbaru in the period 2008 to 2015. This study aims to determine the small industries be featured in a small industrial city of Pekanbaru and where small industries in Pekanbaru City spatially concentrated. This study uses secondary data, employment data is a small industrial branches every district in the city of Pekanbaru. The data were analyzed using descriptive analysis of quantitative analysis tool location quotient (LQ) and spatial concentration. The results of the research with the analysis of location quotient on employment show that in 2008 and 2015 small industries into a small industry featured in Pekanbaru City ie industrial branches of small craft in which branches of industry such craft is superior in District Tampan, District Bukit Raya, District Marpoyan Damai, Distric Tenayan Rayat, District Lima Puluh, District Sail, District Pekanbaru Kota, District Sukajadi, District Rumbai, and District Rumbai Pesisir. Based on the calculation of spatial concentration, a small industrial city of Pekanbaru concentrated in District Payung Sekaki on branch small industrial metals.Keywords : Industrial Base, Spatial Concentration, Location Quotient (LQ) Small Industry